Poly(divinylbenzene‐alt‐maleic anhydride) nanoparticles as a novel stabilizer for Pickering polymerization of styrene. Issue 20 (11th August 2014) - He, Jian; Chen, Dong; Han, Kai; Huang, Xiaoxia; Wang, Liwei; Deng, Jianyuan; Yang, Wantai
<x xml:space="preserve">Abstract</x> Poly(divinylbenzene‐alt‐maleic anhydride) nanoparticles with a narrow distribution and a diameter of 30 nm act as novel stabilizers in the Pickering emulsion polymerization of styrene. The hydrolyzed PDMNPs with NaHCO3 aqueous solution exhibited a very effective emulsification performance and a remarkably high emulsification efficiency. Raspberry‐like PDMNPs/PS composite polymer particles have been successfully fabricated via copolymerization of pendant vinyl groups of PDMNPs with styrene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>